2002
DOI: 10.1002/cbf.980
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/antioxidant status in blood of patients with malignant breast tumour and benign breast disease

Abstract: The aim of this study was to investigate the alterations in lipid peroxidation and antioxidant enzyme defences in the blood of patients with malignant breast tumour and benign breast disease. Forty patients with malignant breast tumour, 20 patients with benign breast disease and also 20 healthy control subjects were recruited for the study. Malondialdehyde levels in plasma and erythrocytes, and the activities of erythrocyte CuZn-superoxide dismutase, catalase, glutathione peroxidase and glucose-6-phosphate deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 16 publications
1
49
1
2
Order By: Relevance
“…Further, the study populations were markedly different from those in the present study in that a significant percentage of subjects were male, many were smokers, and in the Moller study the mean study subject was >3 decades younger than our participants. The levels of oxidative stress in our study group were not as high as has been suggested for breast cancer patients in other studies (40)(41)(42)(43) and may be related to both the fact that our subjects were recruited, on average, just over two years after breast cancer diagnosis and are considered to be consuming relatively healthy diets since the time of breast cancer diagnosis (37). In fact, the plasma carotenoid concentrations observed in the present study sample are generally higher than those observed in the general population, as reflected in National Health and Nutrition Examination Survey III (44).…”
Section: Discussioncontrasting
confidence: 68%
“…Further, the study populations were markedly different from those in the present study in that a significant percentage of subjects were male, many were smokers, and in the Moller study the mean study subject was >3 decades younger than our participants. The levels of oxidative stress in our study group were not as high as has been suggested for breast cancer patients in other studies (40)(41)(42)(43) and may be related to both the fact that our subjects were recruited, on average, just over two years after breast cancer diagnosis and are considered to be consuming relatively healthy diets since the time of breast cancer diagnosis (37). In fact, the plasma carotenoid concentrations observed in the present study sample are generally higher than those observed in the general population, as reflected in National Health and Nutrition Examination Survey III (44).…”
Section: Discussioncontrasting
confidence: 68%
“…The available evidence indicates that in cases of various types of cancers, there are high levels of antioxidant enzyme activity and deficiencies in antioxidant vitamins. [30][31][32][33][34] The results of the current study revealed that CRC-specific VOCs in blood included the following compounds: phenyl methylcarbamate, ethylhexanol, 6-t-butyl-2,2,9,9-tetramethyl-3,5-decadien-7-yne, and 1,1,4,4-tetramethyl-2,5-dimethylenecyclohexane. The methylated alkanes, such as 1,1,4,4-tetramethyl-2, 5-dimethylene-cyclohexane, that were identified as CRC-specific VOCs in our results were similar to the metabolic biomarkers of melanoma that were identified by Abaffy et al, which include 4-methyl decane, dodecane, and undecane.…”
Section: Discussionmentioning
confidence: 79%
“…Oxidized glutathione (GSSG) is reduced back to GSH by glutathione reductase. [30][31][32][33] Reduced glutathione (GSH) and its redox enzymes are the most important cellular antioxidants and play a major role in protecting cells against oxidative stress caused by ROS. [34] Superoxide dismutases (SOD) are a class of enzymes that catalyze the dismutation of superoxide into oxygen and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%